A 29-dBm OIP3 Dual-Stage Power Amplifier with Analog Pre-Distorter in 0.18 µm CMOS for IoT Transceiver. Issue 3 (4th May 2022) - Mariappan, Selvakumar; Rajendran, Jagadheswaran; Noh, Norlaili Mohd; Ramiah, Harikrishnan
Abstract : A low power consumption linear power amplifier (PA) for Internet of Things (IoT) application is presented. An analog pre-distorter (APD) is integrated to the PA, which consists of an active inductor, driver amplifier, and an RC phase linearizer. When measured with continuous wave signal, the PA produces more than 12 dB power gain from 2.4 to 2.5 GHz. At the centre frequency of 2.45 GHz, the PA's gain is 12.5 dB with peak power added efficiency (PAE) of 25.6% and maximum output power of 13.7 dBm. The OIP3 achieved is 29.2 dBm with supply voltage headroom of 1.8 V. The proposed APD befit to be a solution to reduce the trade-off between maximum linear output power and PAE.